Reflections on SAARC Framework Agreement for Energy Cooperation (Electricity) Vis-a-vis India’s “Guidelines on Cross Border Trade of Electricity” - Pun, Santa Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Despite the Indo-Nepal Electric Power Trade, Cross Border Transmission and Grid Connectivity Agreement of October 2014 and despite the SAARC Framework Agreement on Energy Cooperation (Electricity) of November 2014, the Government of India issued the discriminatory Guidelines on Cross Border Trade of Electricity on December 5, 2016. The Guidelines provide preferential one-time approval for all entities with 51% or more Indian ownership wishing to export electricity from Nepal to India. All other entities, the Guidelines stated, had to undergo the case-to-case basis. Historically, such unilateral actions have always been the modus operandi of India. Despite the regular regional cooperation preaching by India, Nepal will have to, like the Tanakpur and Laxmanpur barrages, BUT accept India’s discriminatory December 2016 Guidelines as her fait accompli! HYDRO Nepal Journal Journal of Water Energy and Environment Issue No: 22 Page: 1-4 Uploaded date: January 14, 2018